Observational Methods for Predicting Embankment Settlement - Kim Huat, Bujang; Hoe, Ng Chung; Munzir, H. A. (Universiti Putra Malaysia Press, 2004)
The one dimensional Terzaghi method is still widely used for prediction of settlement. Its differential equation is solved on the assumption that coefficient of consolidation is a constant, in which case the equation becomes linear. But in reality this equation is non linear because compressibility, permeability and coefficient of consolidation changes with settlement. This is why the capability of predicting the rate of settlement or time-settlement relationship remains rather poor. In this paper a number of high quality long-term field settlement data are used to verify the applicability of the observational methods, namely the hyperbolic and the Asaoka method. The field data were from the Tangkak trial embankment (1987-1996) and the Juru trial embankment (1990-1992). Based on the available settlement record for embankment on soft ground, it can be concluded that the prediction of settlement using the hyperbolic method is significantly improved using the start of construction settlement data, notably after more than 50% of the settlements have occurred. Long-term settlement predicting using the early stage data (6 months or less) could be misleading. The capability of the method can also be diagnosed from the characteristics of the CUIVe plotted. For the case of hyperbolic method, it is evident that if a close linear relation of t/p and p is obtained, then the prediction is seemingly good. Prediction of settlement using the Asaoka method is also improved using larger settlement database.